Characterization and health risk assessment of PM2.5-bound organics inside and outside of Chinese smoking lounges. (November 2017) - Li, Lijuan; Ho, Steven Sai Hang; Chow, Judith C.; Watson, John G.; Lee, Frank S.C.; Cui, Long; Gao, Yuan; Dai, Wenting; Ho, Kin Fai; Huang, Yu; Cao, Junji
Abstract: PM2.5 samples were collected at six indoor public places that contained dedicated smoking lounges. Samples were taken in the smoking lounges, at two indoor locations outside of the lounges, and in outdoor air near the venues. Organic carbon (OC), elemental carbon (EC), and non-polar organic compounds including polycyclic aromatic hydrocarbons (PAHs), n -alkanes ( n -C16 to n -C40 ), iso/anteiso-alkanes (C29 to C33 ), hopanes and phthalate esters (PAEs) were quantified. Average PM2.5 levels of 170.2 ± 85.9 μg/m 3 in the lounges exceeded limits of 25 μg/m 3 set by World Health Organization (WHO); these levels were 5.4 and 3.9 times higher than those indoors and outdoors, respectively. High ratios of OC to PM2.5, OC to EC, and PAHs diagnostic ratios in the lounges indicated contributions from environmental tobacco smoke (ETS). The maximum carbon number (Cmax ) and carbon preference indices (CPI) for n -alkanes showed ETS transport from the enclosed lounges to nearby indoor non-smoking areas. Iso/anteiso-alkanes in the lounges were 876.5 ng/m 3, ∼80 times higher than outdoor levels. 17α(H)-21β(H), 30-norhopane and 17α(H)-21β(H), (22R)-homohopane were much higher in the lounges than outdoor air, but they cannot be directly attributed to ETS. Estimated carcinogenic risks of PAHs in the lounges exceeded the acceptable level of 10 − 6 . Highlights: Although confining smokers to an enclosed area, ETS still migrates to indoor air for non-smokers. The ratio of BaP to BghiP is much higher in the smoking area, indicating the presence of ETS. The health risk to non-smokers outside of the smoking lounges did not exceed guidelines for the areas studied.